Serine protease inhibitor derived from Trichinella spiralis (TsSERP) inhibits neutrophil elastase and impairs human neutrophil functions - Kobpornchai, Porntida; Reamtong, Onrapak; Phuphisut, Orawan; Malaitong, Preeyarat; Adisakwattana, Poom (Frontiers in Cellular and Infection Microbiology, 2022)
During early infection with Trichinella spiralis, host neutrophils destroy newborn larvae migrating in the bloodstream, preventing infection. However, parasites secrete various immunomodulatory molecules to escape the host’s defense mechanisms, allowing them to infect the host and live for long periods. T. spiralis secretes serine protease inhibitors (TsSERPs), which are key inhibitory molecules that regulate serine proteases involved in digestion and inflammation. However, the modulatory roles of TsSERP in the inhibition of neutrophil serine proteases (NSPs) and neutrophil functions are unknown. Therefore, the immunomodulatory properties of recombinant TsSERP1 (rTsSERP1) on NSPs and neutrophil functions were investigated in this study. rTsSERP1 preferentially inhibited human neutrophil elastase (hNE). In addition, incubation of rTsSERP1 with fMLP-induced neutrophils impaired their phagocytic ability. The formation of neutrophil extracellular traps (NETs) was activated with phorbol myristate acetate (PMA), and NETs were dramatically reduced when treated with rTsSERP1. Furthermore, rTsSERP1 suppressed the production of proinflammatory cytokines and chemokines during neutrophil activation, which are essential for neutrophil-mediated local or systemic inflammation regulation. In conclusion, T. spiralis immune evasion mechanisms are promoted by the inhibitory properties of TsSERP1 against neutrophil elastase and neutrophil defense functions, and these might be promising alternative treatment targets for inflammatory disorders.